Legality of the Use of Generative Artificial Intelligence in Library Reference Services: An Analysis of Copyright and the Transformative Use Doctrine - Deni Yusup Permana; Siti Julaeha; Zara Zeysa Kirana; Didi Rosidi; Ade Imelda Madiratih; Dessie Inditasary; Ratih Fatikha Sari (The Easta Journal Law and Human Rights, 2026)
This study aims to provide an in-depth analysis of the legality of the use of Generative Artificial Intelligence in the context of academic library reference services, with a particular focus on Law Number 28 of 2014 on Copyright and the doctrine of transformative use. The research employs a normative juridical method using statutory, conceptual, and comparative approaches, drawing upon primary, secondary, and tertiary legal materials. The findings indicate that, although Generative Artificial Intelligence offers revolutionary efficiency in information retrieval and knowledge management, there exists a legal gap regarding the status of artificial intelligence as a legal subject of authorship in Indonesia, as Article 1 point 2 of Law Number 28 of 2014 explicitly requires human involvement. The use of copyrighted data for artificial intelligence training (data scraping) potentially infringes upon the economic rights of authors as stipulated in Article 9 of the same law. However, such use may be justified through a progressive interpretation of the transformative use doctrine within the framework of copyright limitations for educational and research purposes as provided under Article 44 paragraph (1). In conclusion, the legality of Generative Artificial Intelligence utilization in libraries largely depends on its non-commercial purpose and the role of librarians as ethical gatekeepers. Therefore, adaptive regulatory frameworks are required to balance the protection of authors’ exclusive rights with the advancement of information technology innovation in the digital era.